2019
DOI: 10.20448/804.4.1.62.69
|View full text |Cite
|
Sign up to set email alerts
|

Developing Responsibility for Learning in Higher Education in Tanzania: Experiences from Undergraduate Programmes

Abstract: In recent years, the requirement for students to shoulder responsibility for learning has been conceived as one of important attributes of a student or a graduate. This attribute is assumed to be developed through the application of competence-Base Model (CBM) in higher education as opposed to the application of the Traditional Model (lecture to seminar model) practiced in higher education for centuries. Given the importance of shouldering the responsibility for learning among students, particularly, in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…From the analysis of several international journal articles, it is indicated that CTS for students in accounting and LR students in general is relatively inadequate and important to develop (Abdel Razeq, 2014;Allan, 2006;Carpenter & Pease, 2013;Gautam, Jangam, & Loh, 2018;He, Craig, & Wen, 2013;Irafahmi et al, 2018;Kinyaduka, Kalimasi, & Heikkinen, 2019;Sin, Jones, & Wang, 2015;Thompson & Washington, 2015;Wolcott & Sargent, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis of several international journal articles, it is indicated that CTS for students in accounting and LR students in general is relatively inadequate and important to develop (Abdel Razeq, 2014;Allan, 2006;Carpenter & Pease, 2013;Gautam, Jangam, & Loh, 2018;He, Craig, & Wen, 2013;Irafahmi et al, 2018;Kinyaduka, Kalimasi, & Heikkinen, 2019;Sin, Jones, & Wang, 2015;Thompson & Washington, 2015;Wolcott & Sargent, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the transition between languages has a negative effect on academic performance [82 p1262]. Research by Kinyaduka & Kirwa [85] discovered that most students (69.5%) did not fully understand subject content when taught in English, while 78.9% of teachers regard English language instruction as a hindrance to academic achievement. Recognising the language of instruction challenge, recently, in 2017, Tanzania adopted Swahili as the only language of instruction in schools [86,87].…”
Section: First Literacy Language As Scaffolding Toolmentioning
confidence: 99%
“…This is because it carries and translates the expectations of society from an education system into reality (Offorma, 2010). In Tanzania, diversified curriculum today appears to be the best preference among Tanzanians (Kinyaduka, 2013). Therefore, as higher learning institutions, we may need to rethink about our curricula to create a society potential for industrialization.…”
Section: Diversified Curriculum and Industrialisationmentioning
confidence: 99%